Analyzing Barriers to Mentee Activity in a School-Based Talent Mentoring Program: A Mixed-Method Study - Daunicht, Tina-Myrica; Emmerdinger, Kathrin Johanna; Stoeger, Heidrun; Ziegler, Albert (Education Sciences, 2025)
Studies on talent development show that attaining expertise relies on long-term active engagement with a domain. Mentoring plays a key role in this, but it usually takes place outside of school in informal mentoring relationships, and research on formal school-based talent development mentoring programs is lacking. In the present research, we examined which factors in a novel school-based Learning Pathway Mentoring program hinder mentees’ active engagement with their domain. Due to a lack of corresponding research, we employed an exploratory sequential mixed-methods design (QUAL → quan). We first explored factors affecting mentees’ engagement from the perspective of 55 mentors in the Learning Pathway Mentoring program. The results of these qualitative analyses served to derive research questions about variables associated with decreased mentee domain activity, which we then studied in auxiliary quantitative analyses based on a sample of 48 mentees of the same program. Our combined analyses suggest that reasons for decreased mentee engagement may, in fact, be very heterogeneous and nuanced. As talent development places a significant demand on mentees in terms of extracurricular engagement, difficulties might occur specifically when mentees are expected to set priorities regarding the implementation of learning activities in their talent domain and simultaneously meet increasing school demands.
CRIS-Team Scopus Importer:2025-03-14
Keywords: engagement; mentoring; mixed method; motivation; talent development